Implementation of the National Nursing Quality Report Initiative in Canada. Issue 4 (October 2015) - Jeffs, Lianne; Doran, Diane; Hayes, Laureen; Mainville, Claude; VanDeVelde-Coke, Susan; Lamont, Lori; Boal, Anne Sutherland
<x xml:space="preserve">Abstract</x> A qualitative study was undertaken to explore the perceptions and experiences of nurse leaders associated with their participation in the pilot testing of a national nursing database. Interviews with 18 participants were conducted and analyzed using a direct content analysis approach. Three themes emerged including selecting, accessing, and uploading indicators; using indicators and monitoring tools for improvement; and perceiving involvement as a catalyst. Study findings may inform quality improvement efforts in health care organizations.